A Modeling and Control approach for a cubic AUV. Issue 23 (2016) - Clement, Benoit; Rui, Yang; Mansour, Ali; Ming, Li
Abstract: This paper presents a control synthesis methodology for a cubic AUV. The modeling part is based on CFD calculation and the control part is based on H ∞ theory, nonlinear compensation, Smith compensation and Kalman filter. It is presented and adapted to Ciscrea AUV for heading control. A comparison with PID controller is given with simulations and sea tests.